General lighting design. Part one : Fundamentals and indoor calculations - Auburn University. Engineering Extension Service ([Auburn, Ala.] : Auburn University, Engineering Extension Service ; New York : Insight Media [distributor], 2007)
This program addresses issues essential to the design of artificial illumination systems. It considers the relationship between light and human vision and shows how to perform lighting calculations by the point source and lumen methods.
Fundamentals -- Light and human vision -- Point source method of lighting calculation (cag) -- Lumen method of lighting calculation (jh3).
DVD format.
Keywords: Lighting; Lighting -- Design; Lighting -- Visual effects